2003
DOI: 10.1002/pmic.200300452
|View full text |Cite
|
Sign up to set email alerts
|

Unmatched masses in peptide mass fingerprints caused by cross‐contamination: An updated statistical result

Abstract: Unmatched masses are often observed in the experimental peptide mass spectra when database searching is performed with the ProFound program. Comparison between theoretical and experimental mass spectra of standard proteins shows that contamination accounts for most of the unmatched masses. In this retrospective analysis, the top 100 most probable contaminating masses, as listed in order of their probability, are statistically filtered out from 118 different experimental peptide mass fingerprinting (PMF) maps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 7 publications
1
35
0
1
Order By: Relevance
“…However, the mass spectroscopy data reported in that paper appear to be in error, as the fragment reported as the GMP-modified peptide was the same size (2225.12 MHz) as a commonly observed methylated trypsin fragment (Ding et al 2003). Moreover, we were not able to detect a guanylylated K29 peptide by mass spectroscopy when the enzyme was incubated with GTP (data not shown).…”
Section: Formation Of An Enzyme-gmp Covalent Intermediatementioning
confidence: 40%
“…However, the mass spectroscopy data reported in that paper appear to be in error, as the fragment reported as the GMP-modified peptide was the same size (2225.12 MHz) as a commonly observed methylated trypsin fragment (Ding et al 2003). Moreover, we were not able to detect a guanylylated K29 peptide by mass spectroscopy when the enzyme was incubated with GTP (data not shown).…”
Section: Formation Of An Enzyme-gmp Covalent Intermediatementioning
confidence: 40%
“…The presence of unassignable mass peaks in MALDI TOF mass spectrometry is not uncommon, and such peaks were also found in our analyses (Ding et al, 2003). In general, contaminating peaks originate from matrix clusters, proteolytic autolysis, or human keratin.…”
Section: Resultsmentioning
confidence: 69%
“…In our previous study (16), in which in 480 manually acquired and analyzed PMFs 69 contaminant masses in the comparable mass range of 900 -3,500 Da were found, 47 masses were assigned to keratins. In another recent study of 118 spectra (23), 71 contaminants in the range of 900 -3,500 Da were found in Ն5% of spectra, and 53 of these were keratins. These results show that although a comparable number of contaminants were found the use of fully automated spot picking, digesting, and spotting can be highly efficient to avoid contaminations with keratin.…”
Section: Spot Nomentioning
confidence: 99%
“…All of these spots were conjointly recognized by serum antibodies when the main spot of GroEL was determined. Matrix peaks were assigned according to calculated ␣-cyano-4-hydroxycinnamic acid clusters (21) and trypsin peaks as described previously (16,23,27). HDPR outliers (italic) were masses that did not follow the half-decimal place rule.…”
Section: Fig 4 Comparison Of a Sector Of An H Pylori 2-de Gel And mentioning
confidence: 99%